Blasting with a Light Touch; Florida State Project 12014-3501 Fort Myers, Florida (307cb8ee-5b0c-48e5-806c-57d316a0ab82) - Doug Wathen; Philip M. E Thomas (International Society of Explosives Engineers, 1996)
The City of Fort Myers needed to replace a 40-year old 42-inch storm sewer line in downtown Fort Myers with a new 54-inch line to accommodate population growth. The old line had to be kept operational while a new line was installed. the contractor spent two months using a drop ball, a hoe ram, and large rippers trying to break the three to four feet of rock that needed to be removed to accommodate the new pipe. Mechanical trenching was considered but was proven to be overly expensive. On very short notice, Ireco of Florida was asked to design and execute a blasting procedure that would allow this project to proceed. Nearby buildings were over 80 years old, three of them containing antique shops specializing in glass antiquities with attorney offices above them. High water table compounded problems with a 20-year old steel water main and clay drainage pipe 15 feet from the new sewer line. Holes had to be drilled within six inches of the edge of the existing pipe to four feet below the pipe on either side of the pipe and blasted. No interruption in the sewer line flow was to be tolerated.